THE SPECIFIC IMPORTANCE OF TEACHING MUSIC TO CHILDREN IN PRESCHOOL EDUCATIONAL INSTITUTIONS - Abduqulov Dilovar Xayitboboyevich (Galaxy International Interdisciplinary Research Journal, 2021)
In the process of development, the child has a special relationship with the world of objects and events created by previous generations of people. The child actively masters all the achievements of mankind. It requires mastering the world of objects, as well as the actions that take place with them, language, interpersonal relationships, the development of motivations, the development of abilities, the direct assistance of adults. Basically, it is from this period that the child's independent activity begins to grow. The upbringing of children of kindergarten age is a period of improving their complex movements, developing basic hygiene, cultural and labor skills, developing speech, and forming the first buds of social morality and aesthetic taste. This article discusses the specifics and importance of teaching music to children in preschool.